Comparison of Methods for the Estimation of the Maximum Oxygen Uptake of Men Drug Addicts - Wang, Kun; Jiang, Haonan; Zhang, Tingran; Yin, Lian; Chen, Xi; Luo, Jiong (Frontiers in Physiology, 2021)
Background: Maximum oxygen uptake (VO2max) is an important respiratory physiological index of the body’s aerobic endurance, especially for special groups such as drug addicts, it is an important indicator for assessing the cardiopulmonary function and formulating exercise prescriptions. Although the cardiopulmonary exercise test (CPX) is a classic method to directly measure VO2max, this method is limited by factors such as cumbersome operating procedures and expensive equipment, resulting in its relatively low applicability. Recently, many studies have begun to focus on the estimation of VO2max, but few studies have focused on drug addicts. Methods: 15 chemically synthesized drug addicts (such as amphetamines) and 15 plant-derived drug addicts (such as heroin) were recruited at the Chongqing Compulsory Isolation and Drug Rehabilitation Center in China. Firstly, directly measure the subject’s VO2max through the CPX. Secondly, after subjects were fully rested, they were required to complete the 30s high leg raise, 1000m walk, and 3min step experiment respectively. Finally, use SPSS21.0 software to perform the correlation and linear regression analysis to verify the estimated effectiveness. Results: 1) Regardless of chemically synthesized or natural plant-derived drug addicts, the years of drug use and walking time of 1000m were significantly negatively correlated with VO2max, the number of 30s high leg raises was a significantly positive correlation with VO2max (P<0.05, P<0.01), the 3min step-index was significantly positively correlated with VO2max (P<0.01, P<0.01). 2) Regression analysis shows that the 30s high leg lift, 1000m walking, and 3min step experiment could effectively estimate the VO2max of chemically synthesized and natural plant-derived drug addicts. 3) Multiple linear regression constructed by the years of drug use combined with the step-index has the highest estimate accuracy for the VO2max of chemically synthesized drug addicts (96.48%), while unary regression equation established by a single step-index has the highest prediction accuracy for the VO2max of natural plant-derived addicts (94.30%). Conclusions: The indirect measurement method could effectively estimate the VO2max of drug addicts, but different measurement methods have certain differences in the estimation accuracy of VO2max of different drug addicts. In the future, the physical characteristics of drug users can be fully considered.